2022
DOI: 10.9734/ajacr/2022/v11i4209
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment of Some Selected Heavy Metals in Agricultural Soils from Katsina State, North-Western Nigeria

Abstract: This work contributes to the monitoring of heavy metal pollution of Agricultural soils, Katsina State Nigeria, using Atomic Absorption Spectrophotometry. The heavy metal contamination of the soil samples were analyzed based on the Geoaccumulation index (Igeo), enrichment factor (EF), contamination factor (CF), pollution load index (PLI) and potential ecological risk index (PERI). The health risks of the evaluated heavy metals were estimated using the Hazard Quotient (HQ) and Hazard Index (HI)) to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…State are increasingly being contaminated with heavy metals via numerous pollution channels such as horticultural practices, mining and automotive exhaust [6][7][8].…”
Section: Farmlands Used For Agricultural Activities In Katsinamentioning
confidence: 99%
“…State are increasingly being contaminated with heavy metals via numerous pollution channels such as horticultural practices, mining and automotive exhaust [6][7][8].…”
Section: Farmlands Used For Agricultural Activities In Katsinamentioning
confidence: 99%
“…are continuously being loaded with heavy metals from several pollution sources, such as agricultural practices, mining and vehicular exhaust [6,7,8]. The northwestern part of Nigeria where Katsina State is located has of recent, recorded a surge in cattle rustling, kidnappings and rural banditry, with most of the bandits been drawn to the region by illicit and artisanal mining [9].…”
Section: Original Research Articlementioning
confidence: 99%
“…"Studies carried out in Katsina State, Nigeria, have reported that agricultural fields used for cultivation in the state are increasingly being polluted with heavy metals through multiple pollution channels such as horticultural practices, mining and automobile exhaust" [6][7][8].…”
Section: Introductionmentioning
confidence: 99%